Comic Studies THE POTENTIAL OF WAYANG RAMAYANA R.A KOSASIH COMICS AS A MEDIA (KOMPLEMENTER) OF JUNIOR HIGH SCHOOL LEARNING IN CENTRAL JAVA - Safira Rizky Rachmania Hadi; Alvanov Zpalanzani Mansoor (Desain Komunikasi Visual, Manajemen Desain dan Periklanan (Demandia), 2021)
Local content for junior high school content in Javanese language lessons is the story of Ramayana. Junior high school curriculum version 2013, uses Kidang Kencana story segment in Ramayana as Basic Competence 3 in Semester 2 outcome, and students have difficulty understanding it due to various factors. On the other hand, R.A Kosasih made a wayang comic titled Rama and Sinta (Ramayana). Therefore, the aim of this research is to examine whether the comic Rama and Sinta (Ramayana) can be used as a learning medium for junior high school students in Central Java. This is a qualitative research with an empirical approach. The results of the analysis show that there are similarities in the contents of the story, characters, settings and the story line of the Ramayana between the Javanese language textbook and the comic. Therefore, it can be concluded that the comic Rama and Sinta (Ramayana) can be used as a learning medium in Javanese language subjects through language translation, because the content is in accordance with the curriculum.